2022
DOI: 10.3390/biomedicines11010016
|View full text |Cite
|
Sign up to set email alerts
|

The Overlap Syndrome of Obstructive Sleep Apnea and Chronic Obstructive Pulmonary Disease: A Systematic Review

Abstract: Chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA) are common diseases that strongly impact the quality and length of life. Their coexistence is determined by overlap syndrome (OS). This systematic review aims to define the significance of these comorbidities according to the current state of knowledge. For this systematic review, we searched PubMed, Scopus, and Cochrane for studies published between 2018 and 26 October 2022, to find original, observational, human studies published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 154 publications
0
10
0
Order By: Relevance
“…The systematic review by Czerwaty et al [ 10 ] suggests that compared to COPD alone or OSA alone, the OS diagnosis considerably increased the likelihood of developing hypertension. The OS patient had a substantially higher occurrence of coronary heart disease (CHD), including myocardial infarction.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review by Czerwaty et al [ 10 ] suggests that compared to COPD alone or OSA alone, the OS diagnosis considerably increased the likelihood of developing hypertension. The OS patient had a substantially higher occurrence of coronary heart disease (CHD), including myocardial infarction.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together with the molecular and clinical evidence, OVS should be recognized early and the diagnosis should not be missed. However, underdiagnosis regarding either OSAS or COPD and OVS as a result, is not rare (20). Although there have been some efforts to identify an inflammatory molecule as a distinguishing biomarker, the and identified lower levels of pre-CPAP ADMA in the OSAS alone group than in the COPD group (24).…”
Section: Discussionmentioning
confidence: 99%
“…OSAS and COPD are both frequent diseases with marked negative impacts on patients’ QOLs, and they can occur together up to the rates of 11–23% ( 20 ). Concurrence of OSAS and COPD in the same patient is called OVS ( 21 ), and due to a couple of deteriorating mechanisms, including but not limited to systemic inflammation, endothelial dysfunction, and tonic increase in sympathetic activity ( 22 ), OVS is associated with a higher number of vascular risk factors; as well as an increased rate of cardiac/cerebrovascular diseases ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“… 4 5 The prevalence of OSA among patients with COPD is between 56.45% and 78%, while the coexistence of COPD in patients with OSA leads to a prevalence of 11.9%–23.2%. 14 Given the large populations of COPD and OSA, it is estimated that there is also a huge potential population of OS in China; however, the specific prevalence or epidemiology of OSA among patients with COPD in China is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, screening assumes crucial importance, given that improved clinical outcomes have been observed in patients with COPD–OSA overlap on receiving treatment. 15 Although studies have demonstrated the feasibility of questionnaires or portable devices to screen for COPD or OSA, 14 18 19 there has been no effective or appropriate method to identify patients with the combination of both COPD and OSA.…”
Section: Introductionmentioning
confidence: 99%